(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the article, the theoretical, scientific and methodical foundations of studying the science of the latest history of Uzbekistan and teaching it to the younger generation, its historical, practical, vital importance, scientific and methodical foundations, educational influence, the latest history of Uzbekistan, its independent republic, political, economic, cultural , issues of its role in the further strengthening of social values are highlighted.